Sistem Informasi Pelayanan Data Pasien pada Laboratorium UPTD Balai Kesehatan Paru Masyarakat (BKPM) Provinsi Maluku - Marliana Budhiningtias Winanti; Meylan Lesnusa (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2019)
The development of globalization brings with significant impact for every layer of society, especially the development of many technologies needed by every human being, not least in the areas of employment such as health, and others. In this case the Public Lung Health Center (BKPM) Maluku province is the center of the health inspection service laboratory. Where every day a lot of people who come from different places to check their condition to obtain the required health outcomes, but the increase in performance of health services is still not properly fit most people's expectations, because of patient data recording system is still done manually, a long time patient data storage system still manually which takes in the search for patient data it is considered not effective, patient examination data processing is still considered a long time because the process is done. Therefore created an information system to assist agencies in addressing the problem and help some of the difficulties that exist. The inspection data processing system designed to help process patient data input, data storage, and so forth process is computerized. The method used a structured and methods of development of information systems data processing desktop-based health care checks are made using the method Prototype, with tools such as system development flowmap, context diagram, DFD and database design tool. Keywords: Information Systems, Health Services, data processing.